Age, Gender, and Preoperative LVEF Influence on ICU Length of Stay After CABG (Majalah Kedokteran Bandung, 2023)
Coronary artery bypass graft (CABG) surgery is a surgical therapy for coronary artery disease (CAD) patients who cannot be solely treated using pharmacological therapy. Patients undergoing CABG surgery require careful postoperative monitoring in the intensive care unit (ICU). This leads to the need for careful selection of patients due to the limited number of ICU beds available. A prolonged stay in ICU could delay surgery for other patients. This retrospective study analyzed how preoperative factors such as age, gender, and preoperative left ventricular ejection fraction (LVEF) may influence patient's length of stay (LOS) in the ICU. For this study, subjects were patients undergoing isolated CABG in Dr. Hasan Sadikin General Hospital Bandung, Indonesia, during the period of January 2019- December 2020 who were selected using the simple random sampling method. The subjects were categorized into
Keywords: Coronary artery bypass surgery; coronary artery disease; intensive care unit